Anti-ultraviolet water-based acrylic runway surface layer material and preparation method thereof

By using the preparation method of ultraviolet water-resistant acrylic runway surface layer material in the runway material, the problem of color yellowing caused by the wear and ultraviolet irradiation of existing runway materials is solved, and the material's wear resistance, UV resistance and flame retardant performance is improved, extending its service life and reducing environmental pollution.

CN119798522AInactive Publication Date: 2025-04-11GUANGDONG PEIQI SPORTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964625.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing runway materials are prone to wear after long-term use, and their color turns yellow and loses color outdoors due to ultraviolet rays, which has a short service life, and organic solvents are prone to volatilization and polluting the environment during construction.

Method used

A UV-resistant water-resistant acrylic runway surface layer material is used. The preparation method includes adding acrylic acid, acrylate, methacrylate, emulsifier and deionized water to the reactor for emulsification, followed by adding anti-ultraviolet additives, modified nanosilicon dioxide and initiator, heating to induce polymerization reaction, and producing a runway surface layer material with excellent wear resistance, ultraviolet resistance and low VOC characteristics.

Benefits of technology

It significantly improves the wear resistance and mechanical properties of the runway surface material, enhances the resistance to UV and flame retardant properties, extends the service life of the material, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an anti-ultraviolet water-based acrylic runway surface layer material and a preparation method thereof, and belongs to the technical field of runway materials. The anti-ultraviolet coating is prepared from the following raw materials in parts by weight: 16 to 20 parts of acrylic acid, 34 to 40 parts of acrylic ester, 22 to 26 parts of metacrylic acid ester, 4 to 6 parts of an emulsifier, 100 to 150 parts of deionized water, 5 to 15 parts of an anti-ultraviolet aid, 20 to 28 parts of modified nano silicon dioxide and 0.1 to 0.3 part of an initiator. The prepared runway surface layer material takes water-based acrylic acid as a matrix, and the water-based environment-friendly VOC content is low; wherein the modified nano silicon dioxide is good in compatibility with a matrix, so that the wear resistance and the mechanical property of the material are greatly enhanced; molecules of the prepared anti-ultraviolet aid contain various functional groups, so that the anti-ultraviolet and flame-retardant properties and a certain degree of wear resistance of the material can be remarkably improved, and the anti-ultraviolet aid has important application value in the technical field of runway materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of runway materials, and in particular relates to an anti-ultraviolet water-based acrylic runway surface material and a preparation method thereof. Background Art

[0002] The plastic track is an indispensable and important facility in modern track and field venues. Compared with the traditional soil track, it has good elasticity, anti-skid, wear resistance, shock absorption, easy site maintenance, bright colors, and neat appearance. This type of track has the following disadvantages: First, the organic solvents (such as xylene or ethyl acetate, etc.) added during the construction process are easy to volatilize, pollute the environment and endanger the health of the construction workers; second, it needs to be prepared and used immediately, which is troublesome to construct and easily causes loss and waste of materials.

[0003] In recent years, acrylic tracks, as a new type of sports venue material, have gradually attracted attention and application in the sports world. Acrylic tracks use water-based acrylic as the surface material. Water-based acrylic resin not only has the advantages of organic solvent-based resins such as excellent acid and alkali resistance and good pollution resistance, but also has the characteristics of low price, safe use, energy saving, and reduced environmental pollution and public hazards. It is a low-VOC green and environmentally friendly material. However, the long-term use of acrylic tracks will cause serious wear of the acrylic surface material, making the service life of the plastic track shorter. Not only that, when acrylic is used outdoors, it is prone to severe yellowing and discoloration due to the long-term influence of ultraviolet rays. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of track material technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an anti-ultraviolet water-based acrylic runway surface material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing an anti-ultraviolet water-based acrylic runway surface material comprises the following steps:

[0007] Acrylic acid, acrylate, methacrylate, emulsifier and deionized water were added into a reaction kettle and emulsified by high-speed shearing for 15 minutes to obtain an emulsion; then, an anti-ultraviolet additive, modified nano-silica and an initiator were added, the temperature was raised to 70°C, and the reaction was kept warm for 2 hours to initiate a polymerization reaction. After the reaction was completed, an anti-ultraviolet water-based acrylic runway surface material was obtained.

[0008] The raw materials are calculated in parts by weight as follows: 16-20 parts of acrylic acid, 34-40 parts of acrylate, 22-26 parts of methacrylate, 4-6 parts of emulsifier, 100-150 parts of deionized water, 5-15 parts of anti-ultraviolet additive, 20-28 parts of modified nano-silicon dioxide, and 0.1-0.3 parts of initiator.

[0009] Furthermore, the emulsifier is one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate.

[0010] Furthermore, the initiator is a water-soluble initiator.

[0011] Furthermore, the modified nano-silicon dioxide is prepared by the following steps:

[0012] Disperse nano-silica in a three-necked flask filled with ethanol aqueous solution, perform ultrasonic treatment for 15 minutes to make the nano-silica evenly dispersed, add γ-methacryloxypropyltrimethoxysilane (silane coupling agent KH-570), gradually heat up to 65°C, react for 5 hours under mechanical stirring, cool to room temperature after the reaction, take out the filter residue after filtration, wash it with anhydrous ethanol 3-4 times, and dry it in a vacuum oven to obtain modified nano-silica.

[0013] Furthermore, the usage ratio of the nano-silica, the ethanol aqueous solution, and γ-methacryloxypropyltrimethoxysilane is 1 g:100 mL:4.6 g.

[0014] The reaction of nano-silica with silane coupling agent KH-570 can introduce unsaturated carbon-carbon double bonds: through this reaction, the hydrophobicity of the nano-silica surface can be improved, and the compatibility of nano-silica with the acrylic matrix can be enhanced, so that the performance of nano-silica can be fully exerted, and the wear resistance and mechanical properties of the matrix can be greatly enhanced.

[0015] Furthermore, the anti-ultraviolet auxiliary agent is prepared by the following steps:

[0016] S1. In a three-necked flask equipped with a thermometer and a stirring device, cyanuric chloride, resorcinol and chlorobenzene were mixed, and the mixture was stirred continuously until the solid was completely dissolved. Aluminum chloride (catalyst) was then added, and the reaction temperature was controlled to be 65° C. The mixture was stirred continuously during the reaction. After the reaction was completed for 4 hours, the mixture was filtered, chlorobenzene was removed by steam distillation, and the mixture was filtered again. The mixture was washed with anhydrous ethanol for 2-3 times and dried in an oven to obtain intermediate 1. The ratio of cyanuric chloride, resorcinol, chlorobenzene and aluminum chloride was 18.2 g:35.3 g:150 mL:39.8 g.

[0017] Under the catalysis of aluminum chloride, cyanuric chloride and resorcinol undergo an alkylation reaction. By controlling the molar ratio of the two to be close to 1:3 and a slight excess of resorcinol, three chlorine groups on cyanuric chloride participate in the reaction to obtain intermediate 1. The specific reaction process is as follows:

[0018]

[0019] S2. In a three-necked flask equipped with a stirring reflux device, dichloromethylphosphine, 2-thiophene methanol, triethylamine (acid binding agent) and N,N-dimethylformamide (DMF) were mixed and stirred uniformly, and the device was placed in a water bath and heated to 60° C. The reaction was kept warm for 4 hours. After the reaction was completed, the mixture was filtered, and toluene was removed by rotary evaporation. The mixture was washed with anhydrous ethanol for 2-3 times and dried in vacuo to obtain intermediate 2; the ratio of dichloromethylphosphine, 2-thiophene methanol, triethylamine and N,N-dimethylformamide was 13.1 g:11.5 g:15 mL:100 mL;

[0020] Under the catalysis of triethylamine, dichloromethylphosphine and 2-thiophene methanol undergo a nucleophilic substitution reaction. By controlling the molar ratio of the two to be close to 1:1 and the dichloromethylphosphine to be slightly excessive, only one -Cl on the dichloromethylphosphine participates in the reaction to obtain intermediate 2. The specific reaction process is shown below:

[0021]

[0022] S3, in a three-necked flask equipped with a stirring device, intermediate 2, intermediate 1, triethylamine and toluene were mixed and stirred uniformly, nitrogen was introduced as a protective gas, the reaction temperature was controlled to be 80°C, the reaction was kept warm for 6 hours, the reaction was completed, triethylamine hydrochloride was filtered out, part of the solvent was removed by rotary evaporation, and then purified by column chromatography (eluent using a mixed solvent of ethyl acetate / benzene, the volume ratio of the two was 2:5), the eluent was removed by rotary evaporation, and vacuum dried to obtain an anti-ultraviolet auxiliary agent; the ratio of the amount of intermediate 2, intermediate 1, triethylamine, and toluene was 62.7g:40.5g:50mL:200mL;

[0023] Triethylamine is used as an acid-binding agent to remove the hydrogen chloride generated by the reaction, accelerate the reaction, and intermediate 2 and intermediate 1 undergo a nucleophilic substitution reaction. By controlling the molar ratio of the two to be close to 3:1 and intermediate 2 to be slightly excessive, three -OH groups on intermediate 1 participate in the reaction to obtain an anti-ultraviolet additive. The specific reaction process is as follows:

[0024]

[0025] The prepared anti-ultraviolet additive is a triazine ultraviolet absorber, which is mainly composed of a triazine ring and is connected with three ortho-hydroxy substituted phenyl groups. After absorbing ultraviolet rays of a specific wavelength, the hydrogen in the hydrogen bond in the molecule and the carbonyl oxygen or the nitrogen atom on the triazine ring form a chelate ring. When the stabilizer absorbs ultraviolet light energy, thermal vibration occurs, the hydrogen bond breaks, and the chelate ring opens, converting the absorbed ultraviolet energy into harmless heat or other energy forms and releasing it, which can greatly enhance the anti-ultraviolet performance of the acrylic matrix, and return to the initial state under non-radiation conditions or heat release conditions, and has good stability. In addition, the anti-ultraviolet additive molecule also contains a thiophene group, a phosphorus element and a benzene ring, among which the thiophene The phenyl group can not only broaden the absorption range of triazine ultraviolet absorbers, but also increase the molar absorption coefficient of triazine ultraviolet absorbers, thereby further improving the anti-ultraviolet performance of the matrix; the introduced phosphorus element will decompose to produce phosphoric acid or polyphosphoric acid during the combustion process. These compounds act as dehydrating agents to promote rapid dehydration and carbonization of the matrix surface, forming a high-viscosity molten glass-like dense carbonized layer. This carbonized layer can reduce the heat conduction from the flame to the condensed phase, thereby playing a flame retardant effect, and can synergize with triazine to significantly enhance the flame retardant properties of the matrix; finally, the anti-ultraviolet additive contains benzene rings. As a rigid structure, the benzene ring can increase the hardness of the matrix and thus enhance the wear resistance.

[0026] Beneficial effects of the present invention:

[0027] 1. The runway surface material prepared by the present invention is based on water-based acrylic acid, and has a low water-based environmentally friendly VOC content;

[0028] 2. Nano-silicon dioxide is used as filler and modified. Compared with ordinary nano-silicon dioxide, it has better compatibility with the matrix and greatly enhances the wear resistance and mechanical properties of the material;

[0029] 3. The obtained anti-ultraviolet additive molecules contain various functional groups, which can significantly improve the anti-ultraviolet and flame retardant properties of the material and a certain degree of wear resistance;

[0030] Therefore, the runway surface material prepared by the present invention has excellent wear resistance and mechanical properties, high-efficiency anti-ultraviolet and flame retardant properties, and is water-based and environmentally friendly, and has important application value in the field of runway material technology. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Embodiment 1

[0033] Preparation of anti-ultraviolet additives:

[0034] S1. In a three-necked flask equipped with a thermometer and a stirring device, 18.2 g of cyanuric chloride, 35.3 g of resorcinol and 150 mL of chlorobenzene were mixed and stirred continuously until the solid was completely dissolved. Then 39.8 g of aluminum chloride was added and the reaction temperature was controlled to be 65° C. The reaction was stirred continuously during the reaction. After reacting for 4 h, the reaction was completed, filtered, chlorobenzene was removed by steam distillation, filtered again, washed twice with anhydrous ethanol, and dried in an oven to obtain intermediate 1.

[0035] S2. In a three-necked flask equipped with a stirring reflux device, 13.1 g of dichloromethylphosphine, 11.5 g of 2-thiophene methanol, 15 mL of triethylamine and 100 mL of N,N-dimethylformamide were mixed and stirred evenly, and the device was placed in a water bath and heated to 60°C. The reaction was kept warm for 4 hours. After the reaction was completed, the product was filtered, the toluene was removed by rotary evaporation, the product was washed with anhydrous ethanol for 3 times, and the product was dried in vacuo to obtain intermediate 2.

[0036] S3. In a three-necked flask equipped with a stirring device, 62.7 g of intermediate 2, 40.5 g of intermediate 1, 50 mL of triethylamine and 200 mL of toluene were mixed and stirred evenly, nitrogen was introduced as a protective gas, the reaction temperature was controlled to 80 ° C, and the reaction was kept warm for 6 hours. After the reaction was completed, the triethylamine hydrochloride was filtered out, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two was 2:5), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain an anti-ultraviolet auxiliary agent.

[0037] Embodiment 2

[0038] Preparation of anti-ultraviolet additives:

[0039] S1. In a three-necked flask equipped with a thermometer and a stirring device, 36.4 g of cyanuric chloride, 70.6 g of resorcinol and 300 mL of chlorobenzene were mixed and stirred continuously until the solid was completely dissolved. Then 79.6 g of aluminum chloride was added and the reaction temperature was controlled to be 65° C. The mixture was stirred continuously during the reaction. After reacting for 4 h, the reaction was completed, filtered, chlorobenzene was removed by steam distillation, filtered again, washed twice with anhydrous ethanol, and dried in an oven to obtain intermediate 1.

[0040] S2. In a three-necked flask equipped with a stirring reflux device, 26.2 g of dichloromethylphosphine, 23.0 g of 2-thiophene methanol, 30 mL of triethylamine and 200 mL of N,N-dimethylformamide were mixed and stirred evenly, and the device was placed in a water bath and heated to 60° C. The reaction was kept warm for 4 hours. After the reaction was completed, the product was filtered, the toluene was removed by rotary evaporation, the product was washed with anhydrous ethanol for 3 times, and the product was dried in vacuo to obtain intermediate 2;

[0041] S3. In a three-necked flask equipped with a stirring device, 125.4 g of intermediate 2, 81.0 g of intermediate 1, 100 mL of triethylamine and 400 mL of toluene were mixed and stirred evenly, nitrogen was introduced as a protective gas, the reaction temperature was controlled to 80°C, and the reaction was kept warm for 6 hours. After the reaction was completed, triethylamine hydrochloride was filtered out, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two was 2:5), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain an anti-ultraviolet auxiliary agent.

[0042] Embodiment 3

[0043] Preparation of modified nano-silica:

[0044] Disperse 1 g of nano-silica in a three-necked flask filled with 100 mL of ethanol-water solution, perform ultrasonic treatment for 15 min to make the nano-silica evenly dispersed, add 4.6 g of γ-methacryloxypropyltrimethoxysilane, gradually heat to 65 °C, react for 5 h under mechanical stirring, cool to room temperature after the reaction, take out the filter residue after filtration, wash it 3 times with anhydrous ethanol, and dry it in a vacuum oven to obtain modified nano-silica.

[0045] Embodiment 4

[0046] 16 g of acrylic acid, 34 g of acrylate, 22 g of methacrylate, 4-6 g of sodium dodecylbenzene sulfonate and 100 g of deionized water were added to a reaction kettle, and high-speed shearing was performed for 15 min to emulsify and obtain an emulsion; then 5 g of the anti-ultraviolet auxiliary agent prepared in Example 1, 20 g of the modified nano-silica prepared in Example 3 and 0.1 g of azodiisopropylimidazoline were added, the temperature was raised to 70° C., and the reaction was kept warm for 2 h to initiate a polymerization reaction. After the reaction was completed, an anti-ultraviolet water-based acrylic runway surface material was obtained.

[0047] Embodiment 5

[0048] 18 g of acrylic acid, 37 g of acrylate, 24 g of methacrylate, 5 g of sodium dodecyl sulfate and 125 g of deionized water were added to a reaction kettle, and high-speed shearing was performed for 15 min to emulsify and obtain an emulsion; then 10 g of the anti-ultraviolet auxiliary agent obtained in Example 2, 24 g of the modified nano-silica obtained in Example 3 and 0.2 g of azodiisopropylimidazoline were added, the temperature was raised to 70° C., and the reaction was kept warm for 2 h to initiate a polymerization reaction. After the reaction was completed, an anti-ultraviolet water-based acrylic runway surface material was obtained.

[0049] Embodiment 6

[0050] 20 g of acrylic acid, 40 g of acrylate, 26 g of methacrylate, 6 g of sodium dodecyl sulfate and 150 g of deionized water were added to a reaction kettle, and high-speed shearing was performed for 15 min to emulsify and obtain an emulsion; then 15 g of the anti-ultraviolet auxiliary agent obtained in Example 2, 28 g of the modified nano-silica obtained in Example 3 and 0.3 g of azobisisopropylimidazoline were added, the temperature was raised to 70° C., and the reaction was kept warm for 2 h to initiate a polymerization reaction. After the reaction was completed, an anti-ultraviolet water-based acrylic runway surface material was obtained.

[0051] Comparative Example 1

[0052] The anti-ultraviolet auxiliary agent in Example 6 was replaced by a commercially available anti-ultraviolet agent of equal quality, and the remaining steps were the same as those in Example 6.

[0053] Comparative Example 2

[0054] Use commercially available water-based acrylic paint.

[0055] The following performance tests were performed on Examples 4, 5, 6 and Comparative Examples 1 and 2:

[0056] Adopt national standard GB / T 1720 "Determination of paint film adhesion" to measure adhesion;

[0057] The anti-ultraviolet performance is measured according to the national standard GB / T 1865-2009 and rated according to the GB / T 1766 standard;

[0058] The national standard GB 12441-2005 "Surface fire retardant coating" is used to measure the flame retardant time and mass loss;

[0059] The wear resistance was measured using the national standard GB / T 1768 "Determination of abrasion resistance of paints and varnishes - Rotating rubber grinding wheel method";

[0060] The measurement results are shown in the following table:

[0061]

[0062] It can be seen from the above table that the wear resistance, UV resistance and flame retardancy of the runway surface material prepared in the embodiment of the present invention are better than those of the comparative example. Therefore, the present invention has important application value in the field of runway material technology.

[0063] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an anti-ultraviolet water-based acrylic runway surface material, characterized in that: The following steps are involved: Acrylic acid, acrylate, methacrylate, emulsifier and deionized water were added into a reaction kettle and emulsified by high-speed shearing for 15 minutes to obtain an emulsion; then, an anti-ultraviolet additive, modified nano-silica and an initiator were added, the temperature was raised to 70°C, and the reaction was kept warm for 2 hours to initiate a polymerization reaction. After the reaction was completed, an anti-ultraviolet water-based acrylic runway surface material was obtained.

2. The method for preparing a UV-resistant water-based acrylic runway surface material according to claim 1, characterized in that: The anti-ultraviolet auxiliary agent is prepared by the following steps: S1. Mix cyanuric chloride, resorcinol and chlorobenzene, stir continuously until the solid is completely dissolved, then add aluminum chloride, stir and react at 65°C for 4 hours, the reaction is complete, filter, steam distill, filter again, wash, and dry in an oven to obtain intermediate 1; S2, dichloromethylphosphine, 2-thiophene methanol, triethylamine and N,N-dimethylformamide were mixed and stirred evenly, and the mixture was kept at 60° C. for 4 h. After the reaction was completed, the mixture was filtered, rotary evaporated, washed, and vacuum dried to obtain intermediate 2; S3. Mix and stir intermediate 2, intermediate 1, triethylamine and toluene evenly, introduce nitrogen as protective gas, keep warm at 80°C for 6 hours, and after the reaction is completed, filter, rotary evaporate, purify by column chromatography, rotary evaporate, and vacuum dry to obtain an anti-ultraviolet additive.

3. The method for preparing a UV-resistant water-based acrylic runway surface material according to claim 2, characterized in that: In step S1, the ratio of cyanuric chloride, resorcinol, chlorobenzene and aluminum chloride is 18.2g:35.3g:150mL:39.8g.

4. The method for preparing a UV-resistant water-based acrylic runway surface material according to claim 2, characterized in that: In step S2, the ratio of the amount of dichloromethylphosphine, 2-thiophene methanol, triethylamine, and N,N-dimethylformamide is 13.1 g: 11.5 g: 15 mL: 100 mL.

5. The method for preparing a UV-resistant water-based acrylic runway surface material according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 2, intermediate 1, triethylamine and toluene is 62.7 g:40.5 g:50 mL:200 mL.

6. The method for preparing a UV-resistant water-based acrylic runway surface material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 16-20 parts of acrylic acid, 34-40 parts of acrylate, 22-26 parts of methacrylate, 4-6 parts of emulsifier, 100-150 parts of deionized water, 5-15 parts of anti-ultraviolet additive, 20-28 parts of modified nano-silicon dioxide, and 0.1-0.3 parts of initiator.

7. The method for preparing a UV-resistant water-based acrylic runway surface material according to claim 1, characterized in that: The modified nano silicon dioxide is prepared by the following steps: Nano-silica was dispersed in a three-necked flask filled with ethanol aqueous solution, and ultrasonic treatment was performed for 15 minutes to make the nano-silica evenly dispersed. γ-methacryloxypropyltrimethoxysilane was added, and the temperature was gradually raised to 65°C. The mixture was reacted for 5 hours under mechanical stirring. After the reaction was completed, the mixture was cooled to room temperature, and the residue was collected after filtration, washed, and dried to obtain modified nano-silica.

8. A UV-resistant water-based acrylic runway surface material, characterized in that: Prepared according to the method according to any one of claims 1 to 7.